Women’s representations in advertisements: conceptual explorations / As representações das mulheres em propagandas: explorações conceptuais (Revista de Estudos da Linguagem, 2020)
Abstract: Unlike traditional visions show, metaphors are present not only in literary language, but also in everyday, scientific and philosophical languages. It is through the metaphors that we conceptualize the world and understand the most abstract concepts that we have. Based on this premise, this study investigates the conceptual metaphors found in advertisements of women’s magazines, based on the theories: the theory of conceptual metaphor proposed by Lakoff and Johnson (2002), considerations of Kovecses (2002) about this theory and particular character of metaphors in advertisements, as proposed by Velasco-Sacristán (2010) and Ungerer (2003). The purposes of this research are to examine how the metaphors conceptualize the product advertised and how they reveal the social representation of women. The research was done through analysis of four advertisements taken from the magazines: Nova (Dec. 2008), Marie Claire (Oct. 2008), Cláudia (July 2009) and one advertisement taken from a website, published in 2020. The results show that conceptual metaphors are tools used by propagandists in the creation of advertisements based on stereotypes, representations and ideologies of particular group to which the advertisement is intended. Such resources tend to persuade the reader to purchase the product released.Keywords: metaphor; conceptual metaphor; advertisements.Resumo: Ao contrário do que mostram visões tradicionais, a metáfora não está presente somente na linguagem literária, mas também nas linguagens: cotidiana, científica e filosófica. É por meio das metáforas que nós conceptualizamos o mundo e compreendemos a maioria dos conceitos abstratos que temos. Com base nesse postulado, o presente estudo investiga as metáforas conceptuais presentes em propagandas de revistas femininas, tendo como pressupostos teóricos: a teoria da Metáfora Conceptual, proposta por Lakoff e Johnson (2002), as considerações de Kovecses (2002) acerca dessa teoria e o caráter particular das metáforas em propagandas, como proposto por Velasco-Sacristán (2010) e Ungerer (2003). Os objetivos dessa investigação são verificar o modo como as metáforas conceptualizam o produto divulgado e em que medida elas revelam a representação social da mulher. A pesquisa foi realizada através da análise de duas propagandas, retiradas das revistas: Nova (dez. 2008) e Marie Claire (out. 2008). Os resultados mostram que as metáforas conceptuais são ferramentas utilizadas pelos propagandistas na elaboração das propagandas, com base em estereótipos, representações e ideologias de determinado público-alvo ao qual a propaganda é destinada. Tais recursos tendem a persuadir o leitor a adquirir o produto divulgado.Palavras-chave: metáfora; metáfora conceptual; propagandas.